Guest Editorial Note: Introduction to the Special Issues of the IHEC 2020 Conference - Siva Gowri Pathmanathan; Nur Fariha Mohd Manzor; Nor Eyzawiah Hassan; Tengku Amatullah Madeehah T Mohd; Nuruliza Roslan; Mohd Hafiz Jaafar; Lukman Anwar Arifin (2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]